METHOTREXATE IN RHEUMATOID ARTHRITIS – 2015: NEW FACTS AND IDEAS - E. L. Nasonov (Научно-практическая ревматология)
As new effective biological agents (BAs) are being widely introduced, in the past decade there have been serious changes in the rheumatoid arthritis (RA) strategy: its basis was the treat-to-target concept. It is emphasized that the basic strategy component is active early aggressive therapy with methotrexate (MT) and, if MT monotherapy is inade- quately ineffective, combined therapy with MT and standard disease-modifying antirheumatic drugs or MT and BAs. Although oral MT is more frequently prescribed in randomized placebo-controlled trials (RPCTs) and in clinical practice, there is now a tendency towards the wider use of its subcutaneous formulation. Novel evidence from funda- mental studies dealing with the deciphering of the mechanism of MT action and the materials of numerous RPCTs, observational studies, and national registries substantiate the unique place of MT in the treatment of RA, its complica- tions, and comorbidities. The purpose of the review is to analyze new data on the mechanism of action of MT and its clinical efficacy and safety in rheumatology.